Erratum: Multicenter integrals over long-range operators using Cartesian Gaussian functions [Phys. Rev. A 37, 2834 (1988)] - Schwerdtfeger P; Silberbach H (American Physical Society, 2021)
The group headed by Glover and co-workers [1] came across a rather subtle error in our evaluation of the multicenter integrals over long-range operators using Cartesian Gaussian functions arising from the incorrect use of infinities in the alternating series (39) of our original paper. The correction adds an additional term to (48) and, subsequently, to (37) for the H(1,a) term. To show this, we remember the original limit for the integral in Eq. (34) [subcase 2] and substitute correctly for the integration range (Formula Presented).